The Behavioural Intention Of The United Arab Emirates (Uae) Investors To Adopt Blockchain Technology In Stock Market - Hussein, Jamal Nawaf Mohammad (2025)
Blockchain technology can completely transform the financial sector by increasing security, transparency, and productivity. The united arab emirates (uae) has demonstrated a significant interest in blockchain technology and is moving to implement it in several industries. The decision to adopt blockchain technology in the stock market necessitates the readiness of uae investors, who are considered the primary stakeholders in the market. Therefore, this study investigated the behavioural intention of uae investors to use blockchain technology in the stock market, integrating the unified theory of acceptance and use of technology (utaut) model with variable trust. A questionnaire survey was used to gather information from investors in the uae. The sample’s study consisted of individuals who have experience investing in the uae stock market and are familiar with blockchain technology. Using a quantitative research method, a sample of 274 questionnaires was distributed among the targeted respondents of stock market investors in the uae. To analyse the data, the partial least square (pls) structural equation modelling (sem) approach was employed. The findings of the study showed that factors like performance expectancy, social influence, and trust positively and significantly impact the behavioural intentions of investors. Additionally, the study observed a moderating effect of the investors’ age on the facilitating conditions and their behavioural intention to use blockchain technology.